Relationship between FVC, FEV1, FEV1/ FVC% and oxidative stress in type 2 diabetes mellitus - Tanni, Shomia Farid; Ferdousi, Sultana; Islam, Md Saiful (Journal of Bangladesh Society of Physiologist, 2020)
Background: Diabetes mellitus causes micro and macrovascular disorder with debilitating effects on many organs including lungs. There is pulmonary impairment in type 2 diabetic patients (T2DM) which is usually characterized by restrictive pattern. Increased oxidative stress is associated with type 2 diabetes which may contribute to microvascular and macrovascular complications. Objectives:To assess the relationship between oxidative stress and lung function in patients with type 2 diabetes mellitus. Methods: This cross sectional study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from September’2018 to August’ 2019. For this study, 35 newly diagnosed type 2 diabetic male patients aged 30-50 years and similar age and BMI 35 apparently healthy subjects were enrolled as control. Forced vital capacity (FVC), Forced expiratory volume in 1st second (FEV1) and FEV1/FVC%were assessed by portable spirometer. For evaluation of oxidative stress, plasma malondialdehyde (MDA) and catalase levels were measured by competitive ELISA technique and spectrophotometry. Statistical analysis was done by unpaired ‘t’ test, chi-square test, pearson correlation test and multiple regression analysis as applicable. Results: In this study, the mean percentage of predicted value of FVC and FEV1were significantly lower (p<0.001) in T2DM. In addition restrictive pattern of pulmonary function was found in 65.71% and 14.28% in T2DM and healthy control respectively and the difference was statistically significant. The mean plasma catalase was significantly lower (p<0.01) and plasma MDA was significantly higher (p<0.001) in patients. In addition, FVC showed significant negative correlation and significant association with higher MDA level in T2DM. Moreover, FEV1 also showed significant association with MDA in T2DM. Conclusion: The present study reveals that restrictive pattern of pulmonary impairment is related to oxidative stress in T2DM. J Bangladesh Soc Physiol. 2019, December; 14(2): 69-76